An Integrated Framework for the Contextual Analysis of Indigenous Stories - Yangora, Adam Mani (Universiti Malaysia Sarawak (UNIMAS), 2019)
Indigenous Knowledge (IK) is becoming increasingly important due to its gradual disappearance in many communities. Consequently, there is need to capture and preserve stories which are a rich depiction of memories of past in societies. However, it is vital to understand the concepts of storytelling from indigenous people’s own perception before embarking into any documentation project that seeks to preserve stories. Hence, this research investigates the concepts of storytelling to identify the key aspects of context involved. In addition, the thesis reviewed the multiplicity of ontological representations, to study the possibility of integrative approach for context embedded story structure. Eventually, the researcher was able to formulate an integrative framework, of which the basic contextual parameters are embedded. To this effect, an evaluation framework was proposed. The proposed framework has its root from the Aristotle’s Rhetorical Model, which consists of three learning elements namely; Narrator, Story and Audience. Finally, the framework was conceptually validated to provide a proof of concept by developing an ontology to represent the contextual knowledge of indigenous stories using the proposed framework.